Vapour-mediated sensing and motility in two-component droplets - Cira, N. J.; Benusiglio, A.; Prakash, M. (Nature (London), 2015)
Droplets of mixed water and propylene glycol deposited on clean glass exhibit a contact angle but do not suffer from contact line pinning; their motion can be controlled by the vapour emitted from neighbouring droplets to create a variety of autonomous fluidic machines with integrated sensing and motility capabilities. 'Dancing' droplets aid liquid handling The ability to control the movement of fluid droplets is of practical use in many applications including microfluidic liquid handling. Existing techniques demand large energy gradients on the solid surfaces on which the droplets are placed or a carefully prepared surface to overcome contact line pinning (an effect which usually limits droplet motion). This paper reports a previously unrecognized phenomenon that could provide a convenient means of manipulating fluid droplets. Droplets consisting of two miscible components in which one component has both a higher vapour pressure and higher surface tension than the other — such as water and propylene glycol — exhibit a contact angle when deposited on a high-energy surface (clean glass), but rest on a fluid film so do not suffer from contact line pinning. The droplets are stabilized by evaporation-induced surface tension gradients and can move under the influence of tiny forces, including the vapour emitted by neighbouring droplets. A wide range of interesting interactions is recorded — for example, one droplet bouncing off another, a droplet 'chasing' another in a circle and a rainbow of different droplets sorted according to their surface tensions. Controlling the wetting behaviour of liquids on surfaces is important for a variety of industrial applications such as water-repellent coatings 1 and lubrication 2 . Liquid behaviour on a surface can range from complete spreading, as in the ‘tears of wine’ effect 3 , 4 , to minimal wetting as observed on a superhydrophobic lotus leaf 5 . Controlling droplet movement is important in microfluidic liquid handling 6 , on self-cleaning surfaces 7 and in heat transfer 8 . Droplet motion can be achieved by gradients of surface energy 9 , 10 , 11 , 12 , 13 . However, existing techniques require either a large gradient or a carefully prepared surface 9 to overcome the effects of contact line pinning, which usually limit droplet motion 14 . Here we show that two-component droplets of well-chosen miscible liquids such as propylene glycol and water deposited on clean glass are not subject to pinning and cause the motion of neighbouring droplets over a distance. Unlike the canonical predictions for these liquids on a high-energy surface, these droplets do not spread completely but exhibit an apparent contact angle. We demonstrate experimentally and analytically that these droplets are stabilized by evaporation-induced surface tension gradients and that they move in response to the vapour emitted by neighbouring droplets. Our fundamental understanding of this robust system enabled us to construct a wide variety of autonomous fluidic machines out of everyday materials.